PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) DENGAN MEDIA DAKON PADA MATERI PERKALIAN TERHADAP HASIL BELAJAR PESERTA DIDIK - Rizkina Maulisa; Linda Vitoria; Aida Fitri (Jurnal Dedikasi Pendidikan, 2023)
This study aims to determine the effect of the Realistic Mathematics Education (RME) approach with Dakon media on multiplication material on the learning outcomes of class II students at SDN Grong-grong Kab. Pidie. In this study the researchers used a quantitative approach with the type of research Tru Experiment or real experiment and the model used was the pretest-posttest control group design. the population in this study were all class II students at SDN Grong-grong Kab. Pidie and the samples in this study were 25 class II A students as the experimental class and 22 class II B students as the control class. The data collection technique was carried out using a research instrument in the form of a description test of 5 questions. The data analysis technique was carried out using the t-test at a significant level of 5%, 95% confidence level assisted by SPSS statistics version 25. The results obtained from data processing were significant (2-tailed) 0.000  0.05, which means that the criteria in decision making are rejected and accepted, so that there is an influence of the Realistic Mathematics Education (RME) learning approach with Dakon media on multiplication material on the learning outcomes of class II students at SDN Grong-grong Kab. Pidie.